Selective use of extended criteria deceased liver donors with anatomic variations (2012)
Backgrounds: An ongoing shortage of organs for liver transplantation has led surgeons to continually modify criteria for organ acceptance, which are now defined as extended criteria. The organ shortage becomes more problematic in retransplantation, in which the use of a limited resource such as a liver graft with anatomic variation must be weighed against the risk of a more difficult operation. Case Reports: We report 2 peculiar anatomic variations discovered in deceased donors for whole liver transplantation and confirmed at the back table: 1 with a huge biliary enlargement of the common hepatic duct and 1 with a celiac trunk aneurysm. In the first variation, any potential biliary reconstruction was thought to be at high risk of difficult outflow. The vascular anomaly did not preclude successful performance of a liver retransplantation. Conclusions: We briefly report the use of 2 liver grafts from deceased donors with rare anatomic variations, which is relevant to increasing the liver donor pool. To the best of our knowledge this is the first report of this biliary anomaly. In certain specific settings, strategies based on the appropriate donor-recipient match have allowed the use of grafts that otherwise would have been discarded due to celiac aneurysm. © Ann Transplant, 2012.